Abortion and reproductive performance of cattle in northern Nigeria: A questionnaire survey - Nuru, S.; Dennis, S.M. (1976)
A survey on abortion and reproductive performance in cattle was carried out in the six northern States of Nigeria in 1972-73. Three hundred and nineteen herds with 8,970 breeding cows were sampled. One hundred and thirteen herds reported abortions (35 per cent); the lowest incidence was in local herds in Kano State and the highest was on government ranches. Twenty-six herds reported recurrent or chronic abortion. The majority of abortions in non-government herds were not reported to local veterinary authorities (75.8-100 per cent). Average age at first conception in government herds was 2-5 years and 3.5 years in local herds. The percentage of calf crop was highest in the government herds (67 per cent) compared with local Fulani herds (34.2-54.5 per cent) and the pregnancy rale was almost doubled in the government herds. The percentage of Fulani herds reporting repeat breeding varied from 16-6 to 58-8. Although the survey gave no information as to the causes of abortion or the financial loss, it indicated that bovine aborlion was more widespread in the northern states of Nigeria, than previously thought.